Optimisation of Embodied Carbon and Thermal Performance of Roof Material Selections for Australian Residential Housing - Yuqi Fu; Cynthia Changxin Wang (Buildings)
This research is responding to the latest sustainable development policy for residential housing in Australia, which mandates a minimum R6.0 for roof insulation and a requirement of reporting the embodied carbon footprint for new build residential houses before obtaining development approval. The requirement of thermal resistance (R-value) results in thicker roof material to be used, and inevitably increases the total embodied carbon. This condition has drawn the need for an optimised design to balance the embodied carbon with the required thermal performance. In this paper, a multi-objective, mixed-integer, non-linear mathematical programming model is adopted to perform the optimisation. While mathematical programming is a well-established method in optimisation, a research gap has been observed in its application in optimising roof material selection under the simultaneous constraints of the R-value and volumetric heat capacity (thermal mass). Using a common conventional pitched roof with a timber frame, the study demonstrates how the model identifies material combinations that minimise the total embodied carbon within the specified thermal performance ranges. The unique contribution of this research is integrating thermal mass into the optimisation of roof material selections alongside thermal resistance, and embodied carbon. The findings provide practical recommendations for sustainable material selections across varying R-value and thermal mass ranges, offering a new perspective on roof material selections.